Risk factors for pneumonia in acute stroke patients admitted to the emergency department of a tertiary government hospital - de Castillo, Lennie Lynn C. (Animo Repository, 2017)
Background: Knowledge on the risk factors of developing pneumonia, one of the top causes of mortality in acute stroke patients admitted to a tertiary government hospital, is lacking. Aim and Objective: This study aimed to determine the factors associated with the risk of developing pneumonia in acute stroke patients admitted to the emergency department of a tertiary government hospital. Materials and Methods: A retrospective matched case–control study involving acute stroke patients admitted to the emergency department of a tertiary government hospital with 168 pneumonia patients matched with 168 controls by sex was employed. Age, sex, vascular risk factors, previous hospitalization within the past 3 months, type and location of stroke, need for intubation, length of hospital emergency room stay, National Institute of Health Stroke Scale (NIHSS) score on admission, pre-morbid Modified Rankin Scale (mRS) score, and outcome (mortality, NIHSS score and mRS score at discharge) were obtained from the medical charts. Odds ratios were calculated using a multivariate logistic regression analysis. Among stroke patients developing pneumonia, the type of pneumonia and microorganisms were identified. Results: Smoking, alcohol intake, dysphagia, hemorrhagic stroke, need for intubation, and age were associated with pneumonia. Pneumonia increases the odds of mortality and disability by 14 and 7 times, respectively. Hospital-acquired pneumonia is the most common type with Acinetobacter baumanii and Klebsiella pneumonia as the most common microorganisms identified. Conclusion: Age, alcohol intake, dysphagia, hemorrhagic stroke, and need for intubation increase the risk for post-stroke pneumonia with organisms isolated consistent with nosocomial pneumonia. © 2017, Mr Bhawani Singh. All rights reserved.